Plastic degradation in aquatic environments: a review of challenges and the need for standardized experimental approaches - Brožová, Kateřina; Heviánková, Silvie; Halfar, Jan; Čabanová, Kristina; Valigůrová, Alice (Frontiers in Environmental Science, 2025)
Plastic pollution has a significant impact on ecosystems, primarily due to the formation of microplastics through degradation processes. The degradation of plastic waste in aquatic systems is a key pathway in the formation of microplastics, yet the experimental approaches used to study these processes remain inconsistent and poorly harmonized. This review encompasses over 100 relevant documents, including experimental studies on plastic degradation under laboratory and field aquatic conditions, as well as reviews, standards, and policy reports that contextualize methodological challenges and ongoing standardization efforts. We identify key sources of methodological variation, including material types, particle sizes, exposure durations, environmental settings, and physical–chemical parameters such as UV radiation and mechanical stress. These discrepancies hinder the comparability of results and limit the development of robust, policy–relevant conclusions. Recent progress, including the ISO 24187:2023 standard for microplastic analysis, highlights steps toward harmonization but also underscores remaining gaps for degradation testing. We highlight specific gaps in current practices and propose essential parameters that require harmonization–particularly in long–term degradation testing and the simulation of realistic aquatic conditions. By addressing these methodological inconsistencies, more reproducible results can be achieved, enabling predictive modelling and supporting evidence–based risk assessment. In turn, standardized protocols will provide a stronger foundation for environmental policy and mitigation strategies aimed at reducing microplastic pollution.